Prevalence and factors associated with uptake of pre-exposure prophylaxis amongst women vulnerable to HIV who received HIV antibodies in Antibody Mediated Prevention HVTN703/HPTN081 trial in Harare, Zimbabwe: a cross-sectional study - Bernard Ngara; Bekezela Siziba; Nyaradzo Mavis Mgodi; Tariro Dianah Chawana; Miria Chitukuta; Pamela Grace Mukwekwerere; Muchaneta Bhondai-Mhuri; Zvavahera Mike Chirenje; Felix Godwin Sivukile Mhlanga (BMJ Public Health)
Introduction There is limited evidence on pre-exposure prophylaxis (PrEP) uptake post-trial participation for women vulnerable to HIV. This study investigates the prevalence and factors associated with PrEP uptake post-participation in an HIV prevention trial.Methods Former Antibody Mediated Prevention (AMP) study participants were invited to the three AMP clinical research sites in Zimbabwe after at least a year of exiting the study. The AMP study evaluated the safety and efficacy of Vaccine Research Center 01 broadly neutralising monoclonal antibody in reducing acquisition of HIV-1 infection in women in sub-Saharan Africa. Participants vulnerable to HIV were enrolled and risk reduction counselling was done throughout study participation. In a cross-sectional study, semi-structured interview administered questionnaires were completed. The primary outcome was uptake of PrEP after the study exit.Results From February 2022 to August 2022, out of 434 participants enrolled in the AMP study, a total of 298 were invited and 225 participated in the study; 28% made an attempt to access PrEP after study participation, 20% used PrEP at some point after study participation and 15% were on PrEP at the time of questionnaire administration. PrEP uptake was associated with new sexual partners after study participation and higher average number of sexual encounters in the previous month. Challenges faced in accessing PrEP included those related to the health facility, transport problems and stigma.Conclusion The majority (85%) of former AMP participants were not on PrEP at the time of questionnaire administration. We observed poor uptake of PrEP post-study exit among participants who had received risk reduction counselling through study duration. Measures to improve PrEP uptake should be considered on participants vulnerable to HIV when exiting HIV prevention trials.